Synthesis of Propan-1,3-diones and Chromens - JAMODE, V.S.; A. BABREKAR, SHRILEKHA (Asian Journal of Chemistry, 2010)
The present work deals with the synthesis 1-(2-hydroxy-3,4- benzophenyl)-3-styryl-propan-1,3-diones (3a-3a), 2-bromo/iodo-1- [2-hydroxy-3,4-benzophenyl)-3-styryl-propan-1,3-diones (4a-4f), 2-styryl-7,8-benzophenyl chromones (5a-5c), 3-bromo/iodo-2-styryl chromones (6a-6f). Structure of these compounds were established on the basis of element analysis spectral analysis (IR, 13C NMR).